Upcoming Events - Events, Upcoming (Pharmacognosy Communications)
The following conference dates and details have been provided using currently available information. Due to the Rapidly changing nature of the current COVID-19 pandemic and the changes that may become necessary to due to local regulations and/or to ensure safety, these conferences may change prior to their commencement date. All reasonable attempts have been made to check and ensure the validity of these details. However, potential delegates are recommended to check these details with the conference organisers closer to the commencement date. Furthermore, as different regions and countries have different travel restrictions and requirements, it is strongly recommended that you check the requirements for both your own country and the host country before considering attendance at an international conference.